STRATEGIES TO ENCOURAGE STUDENTS TO PARTICIPATE IN ENGLISH SPEAKING ACTIVITIES AT HAIPHONG SECONDARY VOCATIONAL SCHOOL OF TECHNICAL– PROFESSIONAL TRAINING - Lê, Xuân Hương Trang (ĐHNN, 2017)
This research has been done i n an attempt to encourage students to take part in oral presentations and improve their speaking skill at Hai P hong S econdary Vocational School for Technical – Professional Training.Specifically, the researcher puts focus on students’ attitude towards speaking skill, their degree of participation in classroom speaking activities , reasons that make them hesitant to participate in oral activities, current methods applied to teach speaking as well as teachers’ view of CLT, their attitude towards unwilling speakers and mistake makers , their difficulties in teaching speaking and techniques and activities applied in teaching speaking . The research was carried out among nine teachers and 100 students at Hai Phong Secondary Vocational School for Technical – Professional Training . The data were collected by means of survey questionnaires, classroom observation. It was firstly unveiled from the results that the level of students’ participation in speaking lessons is rather low. Secondly, students’ talking time in speaking lessons is limited. Thirdly, regarding to factors affecting students’ participation in oral activities, there were five main ones namely uninteresting speaking topics, poor background knowledge, lack of confidence, lack of motivation and passive learning style . Fourthly, teachers’ difficulties in teaching speaking was also highlighted . Lastly , the current methods were shown that most of the students feel uncomfortable learning with the teachers’ teaching activities which lead to the inability, or the unwillingness of the students to express themselves through oral activities . Basing on these findings, some implications are recommended for both the teachers and the students.